Water Hyacinth Cellulose/Silk Fibroin Composite Films: Preparation and Characterization - Chaosri, P.; Siripipatthana, P.; Srihanam, P. (Asian Journal of Chemistry, 2020)
This study aimed to extract cellulose from water hyacinth using as material for preparation of cellulose/silk fibroin composite films. Using scanning electron microscope (SEM), the native silk fibroin film has smooth surfaces and homogeneous texture, while the cellulose film has short fiber on its surface with dense in texture. The composite films have different morphologies depending on types of polymer used and hierarchical step of film. FTIR analysis showed that the main functional groups of both cellulose (hydroxyl groups) and silk fibroin (carbonyl and amine groups). The composite films also found the absorption peaks of the functional groups which confirmed the composite of both polymers. This results indicated that both polymers had well compatible via bonding formation between the functional groups. The composite films have the maximum temperature decomposition (Td,max) slightly higher value than that of native silk fibroin film. This suggested that the interaction between silk fibroin and cellulose resulted to increase of thermal stability as well as the flexibility of the film.